Assessing the Psychosocial Determinants of Mental Health Decline Among Bangladeshi University Students During the COVID-19 Pandemic: A Rapid Systematic Review - Hasan, Md Rakibul (Queeva Publishing, 2024)
Background: The COVID-19 epidemic has profoundly impacted the mental health of university students. This review investigates the psychosocial factors contributing to the mental health decline of Bangladeshi university students, particularly in Dhaka city, with the objective of identifying the primary elements exacerbating their mental health issues during the pandemic. Method: Employing a mixed-methods approach, this review integrates quantitative and qualitative data, adhering to PRISMA guidelines. Data were extracted using MeSH keywords from databases such as PubMed, PsycINFO, EMBASE, Medline, and ARU-E-Library. Out of 822 initially identified publications, 24 met the inclusion criteria. Thematic analysis was used to investigate pertinent data, and studies were appraised using CASP and AXIS tools. Data interpretation involved SPSS and R, utilizing descriptive statistics, t-tests, ANOVA, and regression analyses. Results: The review identified critical factors contributing to mental health deterioration, including financial hardships, academic disruption, social isolation, excessive smartphone use, and career instability. High prevalence rates of anxiety (61.2%), depression (64.7%), and stress (52.4%) were found. Inferential statistics revealed significant differences in mental health outcomes across demographic groups, with female students showing a 20% higher risk of anxiety and those living with parents showing a 15% higher risk of depression. Discussion: The results emphasize the multifaceted nature of the mental health challenges that students encounter. The transition to online learning, financial instability, and social isolation were substantial stressors. The review emphasizes the necessity of legislative changes and targeted mental health interventions. Conclusion: To address the mental health crisis among university students, policymakers must reform frameworks and provide support systems, including flexible learning models and targeted mental health interventions, to ensure students’ long-term well-being and academic success.